Analysis of the Special Event Konser 7 Ruang in Building DSS Music's Image - Rosa Arzita Yoelma; Mario Leonardus Soriton; Iren Ayu Nindi (IHSA Institute, 2022)
Konser 7 Ruang is a special event in a form of a virtual music concert arranged by DSS Music, firstly held in April 2020. The initiation of the event was motivated by DSS Music’s concern toward Indonesian music artists and crews impacted financially by the COVID-19 pandemic. This study aims to analyze and describe how the implementation of Konser 7 Ruang builds the image of DSS Music as the organizer, as well as to find out what obstacles occurred during the implementation and the efforts deployed to overcome them. The theories and concepts used within this study are public relations, event management process, new media, and image. This study is analyzed and described using a qualitative method with a descriptive approach. The data collection method used in this study was an in-depth interview, supported by documents and literature studies. The data obtained was checked using the triangulation of sources. The results of this study indicate that Konser 7 Ruang has been carried out in accordance with the five stages of the event management process and has succeeded in building a positive image of DSS Music as the organizer. The obstacle that occurred during this special event was that some of the performers were new to the technology used in Konser 7 Ruang. DSS Music overcame this problem by educating the performers and negotiating with them .